An oligogalacturonide‐derived molecular probe demonstrates the dynamics of calcium‐mediated pectin complexation in cell walls of tip‐growing structures. (29th May 2017) - Mravec, Jozef; Kračun, Stjepan K.; Rydahl, Maja G.; Westereng, Bjørge; Pontiggia, Daniela; De Lorenzo, Giulia; Domozych, David S.; Willats, William G. T.
Summary: Pectic homogalacturonan (HG) is one of the main constituents of plant cell walls. When processed to low degrees of esterification, HG can form complexes with divalent calcium ions. These macromolecular structures (also called egg boxes) play an important role in determining the biomechanics of cell walls and in mediating cell‐to‐cell adhesion. Current immunological methods enable only steady‐state detection of egg box formation in situ . Here we present a tool for efficient real‐time visualisation of available sites for HG crosslinking within cell wall microdomains. Our approach is based on calcium‐mediated binding of fluorescently tagged long oligogalacturonides (OGs) with endogenous de‐esterified HG. We established that more than seven galacturonic acid residues in the HG chain are required to form a stable complex with endogenous HG through calcium complexation in situ, confirming a recently suggested thermodynamic model. Using defined carbohydrate microarrays, we show that the long OG probe binds exclusively to HG that has a very low degree of esterification and in the presence of divalent ions. We used this probe to study real‐time dynamics of HG during elongation of Arabidopsis pollen tubes and root hairs. Our results suggest a different spatial organisation of incorporation and processing of HG in the cell walls of these two tip‐growing structures. Significance Statement: The properties of plant cell walls depend on fine processing and arrangement of structural polysaccharides such as pectins, including their mutual covalent or non‐covalent interactions. Here we developed a small molecular probe which enables real‐time visualisation of calcium‐mediated crosslinking of homogalacturonan, a major pectin type, and used it to explore the dynamics of pectin in two tip‐growing structures, namely pollen tubes and root hairs.